Grain dust explosions up sharply in 1984 over 1983 - Schoeff, Robert W. (Kansas State University. Dept. of Grain Science and Industry, 2010)
Twenty grain dust explosions were reported in the U.S. to Ralph Regan, F.G.I.S. Safety Director, and Robert W. Schoeff, Extension Marketing and Safety Specialist, Kansas State University. This was a 53% increase over the 1983 low and equal to the 10 year average of 20 explosions.
Keywords: Grain dust; Dust explosions